The Cambridge companion to Montaigne - Langer, Ullrich, ed. (Cambridge : Cambridge University Press, 2005)
Michel de Montaigne (1533-1592) is known for his innovative method of philosophical inquiry which mixes the anecdotal and the personal with serious critiques of human knowledge, politics and the law. This volume explores the range of his philosophy and also examines its social and intellectual contexts
1. Introduction Ullrich Langer; 2. Montaigne's political and religious context Ullrich Langer; 3. Montaigne's legacy Warren Boutcher; 4. Montaigne and antiquity: fancies and grotesques John O'Brien; 5. The Essays and the New World Tom Conley; 6. Justice and the law: on the reverse side of the Essays Andre Tournon; 7. Montaigne and the notion of prudence Francis Goyet; 8. Montaigne and the truth of the schools Ian Maclean; 9. The investigation of nature George Hoffmann; 10. Montaigne and scepticism Ann Hartle; 11. Montaigne on moral philosophy and the good life
Includes bibliographical references (p.229-237) and index
Keywords: Montaigne, Michael de, 1533-1592